Pendampingan Penyusunan Konsep Wisata Berbasis Potensi Lokal pada Objek Wisata Pulau Semut Kelurahan Limbungan - Muthia Anggraini; Alfian Saleh; Virgo Trisep Haris (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Riverside areas have unique and varied characters that are not the same as others in terms of social, economic, cultural, and environmental aspects. The unique and specific character of the Pulau Semut Tourism object located in the Limbungan Village Pengambangan Area can be developed according to its potential. The location is on the side of the river which is still natural because it has a mangrove forest that is still beautiful. The local wisdom of this tourist attraction is that it is managed by the local community, with tourist destinations that are still natural, and there are several local products from fish processing that are worth developing as a local potential-based tourism concept. Partners still need to be assisted in terms of preparing local potential-based tourism concepts. The methods used are the discussion method, activity planning method, and implementation method. The result is that the concept displayed on the map is the local potential, namely the balimau spot and the culinary meatballs of rasau fish. In conclusion, the preparation of the Ant Island tourism concept emphasizes the local potential of Ant Island tourism.